IMMERSION: HOW ANIMATION IS SHAPING THE FUTURE OF HUMAN-COMPUTER INTERACTION (AR/VR/MR) - Saniya Assembek (American Journals Publishing, 2025)
The article examines the role of animation in shaping user experience in immersive technologies: augmented (AR), virtual (VR) and mixed reality (MR). Particular attention is paid to the function of animation as an interface tool that influences perception, navigation, interaction and emotional involvement of the user. The features of the use of animation in various types of XR environments are analyzed, as well as its importance in creating a cognitively comfortable and intuitive digital space. The importance of designing animation taking into account the psychophysiological features of perception and technical limitations of devices is emphasized.